Spanish and English Oral Language Growth Rates of Bilingual Preschoolers: The Effect of Language of Instruction. Issue 3 (22nd August 2022) - Durán, Lillian; Wackerle‐Hollman, Alisha; Miranda, Alejandra; Chávez, Carlos; Pentimonti, Jill; Zyskind, Karen; Rodriguez, Michael C.
Abstract: Studying the oral language growth of Spanish‐speaking preschoolers in the United States is increasingly important given the critical role early language development plays in reading outcomes. In this article, we report on the Spanish and English growth trajectories observed in 124 bilingual preschoolers collected over 2 years in 36 classrooms across 5 states and the associations of growth in each language to language of instruction and home language exposure. Patterns indicate the need for Spanish instruction to maintain robust rates of Spanish growth and English growth rates in Spanish, bilingual, and English‐only instruction. Significant differences in English and Spanish oral language abilities were also noted at the intercept between children who were Spanish dominant versus balanced bilinguals. Implications for research and practice are provided.